SOCIAL ASPECTS OF THE DEVELOPMENT OF COOPERATION “FAMILY – NEIGHBORHOOD – EDUCATIONAL INSTITUTION” - Karimova Gulnoza (Research Focus International Scientific Journal, 2023)
as you know, a person first grows and grows in the family, forms as a person. Family upbringing, spiritual and moral values will later find their place among people, that is, in the neighborhood, in the family, in educational institutions. Therefore, it is impossible to resolve the day of tomorrow of our motherland and people, the grandiose like the coming of age of the perfect generation, which determines the prestige of the world community, without the cooperation of a family-neighborhood-educational institution. In this article, the social aspects of the development of cooperation "family-neighborhood-educational institution" were studied.